A novel method of ultrasound-guided positive staining using indocyanine green fluorescence in laparoscopic anatomical liver resection of segments VII and VIII - Jiang, Zedong; Zhou, Bo; Zheng, Xiang; Li, Guogang; Gao, Zhenzhen; Tian, Yang; Shao, Chunlong; Xu, Shaoyan; Yan, Sheng (Frontiers in Oncology, 2023)
Abstract Background: Recently, in many Asian centers, laparoscopic anatomical liver resection (LALR) using the indocyanine green (ICG) fluorescence imaging technique has been increasingly applied in resecting hepatocellular carcinoma (HCC), even in colorectal liver metastases. However, LALR techniques have not been fully standardized, especially in right superior segments. Herein, we design a novel method of ICG-positive staining to better achieve the staining goal for LALR of right superior segments. Methods: Between April 2021 and October 2022, we retrospectively studied consecutive patients in our institute who underwent LALR of right superior segments using a novel method of ICG-positive staining, which comprised a customized puncture needle and an adaptor. Guided by preoperative three-dimensional (3D) simulation, intraoperative laparoscopic monitoring and laparoscopic ultrasound (LUS) imaging, we punctured the transhepatic needle into the target portal vein through the guide hole (assembled with an adaptor) of the LUS probe (Pro Focus 2202, BK Medical, Herlev, Denmark) and then slowly injected 5-10 ml of 0.025 mg/ml ICG solution into the vessel. LALR can be guided by the demarcation line under fluorescence imaging after injection. Demographic, procedural and postoperative data were collected and analyzed. Results: In this study, 21 patients underwent LALR of the right superior segments with ICG fluorescence-positive staining, among which 6 failed, but the procedures had a success rate of 71.4%. The average staining time was 13.0±6.4 min, the operative time was 230.4±71.7 min, R0 resection was 100%, the postoperative hospital stay was 7.1±2.4 days, and no severe puncture complications occurred. Conclusions: The novel customized puncture needle approach is feasible and safe for ICG-positive staining in LALR of right superior segments, with a high success rate and a short staining time.